Mendorong Kesejahteraan Perempuan: Menjamin Cuti Maternitas melalui Program Jaminan Sosial Ketenagakerjaan - Setyonaluri, Diahhadi; Milawati, Resmi Setia (Yayasan Jurnal Perempuan, 2023)
Indonesia has a statutory paid maternity leave, however it remains restricted to the employer’s liability and has not yet been integrated into the social security system within the labour sector. Prior research suggests that the availability of maternity leave remains restricted, which raises the likelihood of experiencing reduced income during leave and missing out on potential employment chances upon return. The main objective of paid maternity leave is not just to safeguard the women’s needs, but also to improve the welfare of children and families, resulting in favorable economic benefit. This article advocates for the need of transitioning the prevailing perspective on maternity leave, wherein it is seen as the responsibility of the employer, to a social insurance programme that falls within the scope of employment social insurance. Implementing such a programme would guarantee that women have the ability to take time off and get financial support throughout their leave, in order to preserve their well-being, as well as that of their children and families. Additionally, it would provide reassurance for a smooth transition back to work following the completion of maternity leave.